A lack of association between severity of nicotine withdrawal and individual differences in compensatory nicotine self-administration in rats - Harris, Andrew C. (2011)
RATIONALE: Compensatory smoking may represent an adverse consequence of smoking reduction or the use of reduced nicotine tobacco products. Factors contributing to individual variability in compensation are poorly understood. OBJECTIVE: To examine whether severity of nicotine withdrawal as measured by elevated intracranial self-stimulation (ICSS) thresholds is related to individual differences in compensatory nicotine self-administration (NSA) following unit dose reduction. METHODS: Rats were trained for ICSS and NSA (0.06 mg/kg/inf). After stabilization, effects of reducing the nicotine unit dose to 0.03 mg/kg/inf were examined. Following reacquisition of NSA (0.06 mg/kg/inf), effects of antagonist-precipitated withdrawal and saline extinction (spontaneous withdrawal) were examined. RESULTS: Reducing the NSA unit dose produced partial compensation as indicated by increased infusion rates but a 35% mean decrease in daily nicotine intake. Magnitude of compensation varied considerably among rats. Dose reduction did not elicit withdrawal in rats as a group, although there were substantial increases in ICSS thresholds in some animals. Intracranial self-stimulation thresholds were consistently elevated during precipitated and spontaneous withdrawal, confirming that rats were nicotine-dependent. Individual differences in compensation were not correlated with changes in ICSS thresholds during dose reduction, precipitated withdrawal, or spontaneous withdrawal. In a secondary analysis, greater precipitated withdrawal severity predicted greater initial nicotine-seeking during extinction. CONCLUSIONS: Severity of nicotine withdrawal was not related to the degree of compensation in this protocol. These data do not support a role for nicotine withdrawal in individual differences in compensation during reduced nicotine exposure, but do suggest that withdrawal may contribute to nicotine-seeking during early abstinence.